TAFSIR PROGRESIF ATAS KISAH-KISAH DALAM AL-QUR’AN KARYA EKO PRASETYO - Rabbany T, Al-Faiz M; Abror, Indal (UIN Sunan Kalijaga Yogyakarta, 2018)
Kitab Pembebasan is Eko Prasetyo’s first work in the field of interpretation contains the stories of prophets and friends in the Qur'an. For him, the stories of the prophets no longer have the power to change circumstances, then progressive logic brings Eko to an interpretation of the stories of the prophet to the surrounding social problems. When many commentators who interpret the Quran relate to the social community, then interpreting the Quran leads to social criticism being unique to discuss. So this paper is focused on discussing social criticism in the Book of Liberation. In this paper, there are indications of the content of social criticism Eko Prasetyo then grouped them into five fields, namely economics, religion, education, politics and society. Then explained based on the theme specifically. Then develop social criticism based on each theme. Among them is a criticism of the economic system of capitalism, interpretation of the meaning of Satan, tyranny, seditious and idolatrous, religious and financiers, criticism of Suharto and the New Order, the case of the murderous activist Salim deer. Also, Eko's other works were reviewed to develop his criticisms. The interpretation for Eko through the Book of Liberation is the contextualization of the problems that occur around him, Eko does not care about the interpretation of the interpretation, because for Eko, the Qur'an is a book of movements that must be practiced.Keyword: Eko Prasetyo, Progressive Interpretations, Qissah, al-Qur’an